2009
DOI: 10.1038/onc.2009.429
|View full text |Cite
|
Sign up to set email alerts
|

MYCN/c-MYC-induced microRNAs repress coding gene networks associated with poor outcome in MYCN/c-MYC-activated tumors

Abstract: Increased activity of MYC protein-family members is a common feature in many cancers. Using neuroblastoma as a tumor model, we established a microRNA (miRNA) signature for activated MYCN/c-MYC signaling in two independent primary neuroblastoma tumor cohorts and provide evidence that c-MYC and MYCN have overlapping functions. On the basis of an integrated approach including miRNA and messenger RNA (mRNA) gene expression data we show that miRNA activation contributes to widespread mRNA repression, both in c-MYCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
126
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 45 publications
(52 reference statements)
8
126
0
1
Order By: Relevance
“…MiR-9 has also been found to sensitize cells to EMT-inducing signals arising from the TME [129]. Overall, the c-myc-induced miRNA network is reported to be directly related to tumor aggressiveness in various types of cancers [130].…”
Section: Emt and Mirna Regulationmentioning
confidence: 92%
“…MiR-9 has also been found to sensitize cells to EMT-inducing signals arising from the TME [129]. Overall, the c-myc-induced miRNA network is reported to be directly related to tumor aggressiveness in various types of cancers [130].…”
Section: Emt and Mirna Regulationmentioning
confidence: 92%
“…It is not fully established how MYCBP regulates these E-box-containing genes because of growing evidence about the function of MYCBP (Furusawa et al, 2001Yukitake et al, 2002;Ishizaki et al, 2006), but there is evidence suggesting that MYCBP acts, at least in part, through modulating the transactivation activity of c-Myc to enhance the transcription of these genes (Taira et al, 1998;Sakamuro and Prendergast, 1999). Recent studies showed that some c-Myc-mediated miRNAs were implicated in tumorigenesis, embryonic stem cell differentiation and glutamine metabolism (He et al, 2005;O'Donnell et al, 2005;Dews et al, 2006;Chang et al, 2008;Sander et al, 2008;Gao et al, 2009;Lin et al, 2009;Mestdagh et al, 2009). However, only two miRNAs were found to modulate c-Myc, whereas c-Myc is not their significant targets (Sampson et al, 2007;Lal et al, 2009).…”
Section: Mir-22 Might Constitute a Feedback Loop With C-myc And Mycbpmentioning
confidence: 99%
“…The MYCBP (AMY-1) gene encodes a small c-Mycbinding protein of B11 kD, that binds the N-terminal domain of c-Myc through its C-terminal region and stimulates E-box-dependent transcriptional activation of c-Myc to promote tumorigenesis (Taira et al, 1998;Sakamuro and Prendergast, 1999). Several miRNAs have been found to regulate cell proliferation and anchorage-dependent growth (Esquela-Kerscher and Slack, 2006), but cross-talk between miRNAs and Myc genes has only started to emerge (Chang et al, 2008;Mestdagh et al, 2009). In this respect, recent studies have shown that c-Myc acts directly as a regulator of a broad panel of miRNAs including miR-22 (Chang et al, 2008;Mestdagh et al, 2009), but the effects of miRNAs on c-Myc expression and function are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Various miRNAs are overexpressed or underexpressed in different types of cancer in humans and may function as either tumor suppressors or oncogenes. [5][6][7][8][9][10][11][12][13] A cluster of six miRNAs (miR-17-92, comprising miR-17, miR18a, miR-20a, miR-19a, miR-19b-1, and miR-92a-1) is processed from the transcript of C13orf25 (also known as MIR17HG or MIRHG1), a gene amplified in some lymphomas and solid tumors 5,14 -17 and overexpressed in a large fraction of lymphomas. 5 Overexpression of miR-17-92 accelerates lymphomagenesis in mouse models.…”
mentioning
confidence: 99%